Bilateral Neonatal Testicular Torsion; Hidden Surgical Nightmare - Tariq O. Abbas; Tariq O. Abbas; Tariq O. Abbas; Mansour Ali (Frontiers Media S.A., 2018)
Perinatal testicular torsion is a relatively rare event that remains unidentified in many situations and managed only after an avoidable delay of time. Its current management approaches include watchful observation, delayed contralateral orchiopexy, and emergent contralateral orchiopexy. On the other hand, bilateral torsion is now being more frequently reported. However, the assessment of the contralateral testis through physical examination and imaging can be inaccurate in cases of perinatal torsion. We report a case of prenatal testicular torsion with incidentally discovered metachronous contralateral extravaginal testicular torsion. Therefore, immediate surgical intervention is recommended both when uni- or bilateral testicular torsion is suspected. Whenever possible, affected testes should be preserved as some endocrine function may be retained.